Plasma Alkylresorcinols Reflect Gluten Intake and Distinguish between Gluten-Rich and Gluten-Poor Diets in a Population at Risk of Metabolic Syndrome. Issue 10 (14th September 2016) - Lind, Mads V; Madsen, Mia L; Rumessen, Jüri J; Vestergaard, Henrik; Gøbel, Rikke J; Hansen, Torben; Lauritzen, Lotte; Pedersen, Oluf B; Kristensen, Mette; Ross, Alastair B
Abstract: Background: Many patients with celiac disease experience difficulties in adherence to a gluten-free diet. Methods for testing compliance to a gluten-free diet are costly and cumbersome. Thus, a simple biomarker of gluten intake is needed in a clinical setting and will be useful for epidemiologic studies investigating wider effects of gluten intake. Objective: The aim was to evaluate plasma total alkylresorcinol concentrations as a measure of gluten intake. Methods: In this randomized, controlled, crossover intervention study in 52 Danish adults with features of the metabolic syndrome, we compared 8 wk of a gluten-rich and gluten-poor diet separated by a washout period of ≥6 wk. We measured fasting plasma concentrations of alkylresorcinols to determine if they reflected differences in gluten intake as a secondary outcome of the original study. In addition, we investigated in 118 Danish adults the cross-sectional association between self-reported gluten intake and plasma alkylresorcinols in the same and a similar study at baseline. We used mixed-model ANCOVA for examining treatment effects, a classification tree to determine compliance to the gluten-poor diet, and linear regression models for examining baseline correlation between plasma alkylresorcinol concentrations and gluten intake. Results: Plasma total alkylresorcinols decreased more during the gluten-poor period (geometric mean: –124.8 nmol/L; 95% CI: –156.5, –93.0 nmol/L) than in the gluten-rich period (geometric mean: –31.8 nmol/L; 95% CI: –63.1, –0.4 nmol/L) ( P < 0.001). On the basis of the plasma alkylresorcinol profile, we built a classification tree to objectively determine compliance and found an overall participant misclassification error of 3.9%. In the cross-sectional study we found a 5.6% (95% CI: 2.4%, 8.9%) increase in plasma total alkylresorcinols per 1-g increase in reported gluten intake ( P < 0.001). Conclusion: We propose the use of plasma alkylresorcinols to monitor compliance to a gluten-free diet as well as to help investigations into the possible effects of gluten in the wider population. This trial was registered at www.clinicaltrials.gov as NCT017119913 and NCT01731366.